2009
DOI: 10.1002/0471143030.cb2404s42
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Cellular Phosphoinositide Pools with GFP‐Fused Protein‐Domains

Abstract: This unit describes the method of following phosphoinositide dynamics in live cells. Inositol phospholipids have emerged as universal signaling molecules present in virtually every membrane of eukaryotic cells. Phosphoinositides are present in only tiny amounts as compared to structural lipids, but they are metabolically very active as they are produced and degraded by the numerous inositide kinase and phosphatase enzymes. Phosphoinositides control the membrane recruitment and activity of many membrane protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 102 publications
2
73
0
Order By: Relevance
“…To evaluate whether there was a similar correlation between actin and PIP 2 during the recovery of cortical actin density at the synapse, we cotransfected CTLs with Lifeact-mApple and Tubby-EGFP (30,31) and performed TIRF imaging on CTLs as they formed synapses on a planar activating surface. At early time points during interaction with anti-CD3-coated surfaces, we observed that the reduction in cortical actin density at the center of the synapse was concurrent with a reduction in levels of PIP 2 , consistent with our previous CTL-target conjugate imaging ( Fig.…”
Section: Acute Pip 2 Ablation Results In the Rapid Disassembly Of Cormentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate whether there was a similar correlation between actin and PIP 2 during the recovery of cortical actin density at the synapse, we cotransfected CTLs with Lifeact-mApple and Tubby-EGFP (30,31) and performed TIRF imaging on CTLs as they formed synapses on a planar activating surface. At early time points during interaction with anti-CD3-coated surfaces, we observed that the reduction in cortical actin density at the center of the synapse was concurrent with a reduction in levels of PIP 2 , consistent with our previous CTL-target conjugate imaging ( Fig.…”
Section: Acute Pip 2 Ablation Results In the Rapid Disassembly Of Cormentioning
confidence: 99%
“…One of the key enzymes downstream of the TCR is phospholipase C gamma 1 (PLCγ1), which cleaves PIP 2 into inositol 1,4,5-triphosphate (IP 3 ) and diacylglycerol (DAG), two critical intermediates required for T-cell activation that trigger Ca 2+ flux and cell polarization changes, respectively (2,28,29). To address whether inhibition of PLCγ1 could modify local levels of its substrate, PIP 2 , at the synapse, we cotransfected CTLs with Lifeact-mApple and a sensor expressing the PIP 2 -binding domain of Tubby fused to EGFP (Tubby-EGFP) (30,31). We then pretreated cells with either U-73122, an inhibitor of PLCγ1 activity, or U-73343, an inactive analog (32), and allowed CTL-target conjugates to form before fixation.…”
Section: Pharmacological Inhibition Of Phospholipase C Gamma 1 Inhibimentioning
confidence: 99%
“…EGFP-lactadherin-C2, developed by the Grinstein laboratory (27), was obtained from Addgene. PLC␦1-PH-GFP was a generous gift from Tamas Balla (29,30).…”
Section: Methodsmentioning
confidence: 99%
“…Single molecule TIRF microscopy assays in live cells indicate that mutations to either the NTM or the CTM reduce the Myo1a-TH1 membrane-bound lifetime. Finally, although Myo1a-TH1 co-localizes with both the PS-binding protein, lactadherin C2 (27,28), and the PI(4,5)P 2 -binding protein, PLC␦1-PH (29,30), only lactadherin C2 is able to compete with Myo1a for targeting to microvilli. Together, our results suggest that Myo1a targeting to microvilli is driven by membrane binding potential that is distributed throughout TH1 rather than localized to a single motif.…”
mentioning
confidence: 96%
“…The PH domain of PLCδ1 (Phospholipase C δ1) that specifically binds to PI(4,5)P 2 is a well-established probe for imaging PI(4,5)P 2 sub-cellular distribution and dynamics 33,34 in the PM. We have genetically tagged this domain with two fluorescent proteins, PAmCherry1 35 and iRFP 36 to 1.…”
Section: Introductionmentioning
confidence: 99%